An Introduction to Teaching - Lueck, William R. (New York: Holt, 1953)
This handbook provides basic information about adult learning as it relates to acquiring another language. It is intended to serve as an introduction to more comprehensive study for instructors and tutors. The guide provides some information on the following subjects: (1) an outline of reasons for adapting existing textbook material and indications of ways to adapt dialogs and other language activities; (2) a discussion of the principles of adult learning and characteristics of adults that affect the learning process; (3) a brief presentation of the elements of language, that is, meaning, grammar, sound system and social usage, and principles of language learning; and (4) the role of the instructor and some instructional techniques. The final section also includes several lesson plans dealing with listening comprehension, oral practice, the sounds and music of the language, vocabulary, pattern practice, visual aids, reading, spelling, and writing. A summary, review questions, and a selected bibliography complete the volume. (AMH)
Includes Index.
Microfiche.
Keywords: Adult Education; Adult Learning; Adult Students; Audiolingual Skills; Class Activities; English (Second Language); Language Patterns; Language Usage; Learning Activities; Lesson Plans; Reading Instruction; Second Language Instruction; Spelling Instruction; Teacher Effectiveness; Teaching Guides; Teaching Methods; Visual Aids; Vocabulary Skills; Writing Instruction; Guides, Classroom -- Teacher